Engineering the mechanical properties of CNT/PEEK nanocomposites. Issue 23 (25th April 2019) - Wang, Bo; Zhang, Ke; Zhou, Caihua; Ren, Mingfa; Gu, Yuantong; Li, Tong
Abstract : The mechanical properties of the CNT/PEEK composite can be modulated by the functionalization of CNT reinforcements. Abstract : Poly-ether-ether-ketone (PEEK) was deeply investigated as a composite matrix because of its outstanding mechanical properties and thermostability. However, the performance improvement of fiber-reinforced PEEK composites was moderate according to a great number of experimental investigations. An insightful understanding of the deformation and interfacial failure in the PEEK composite is needed to guide the future fabrication of high-performance PEEK plastics. In this paper, Molecular Dynamics (MD) simulation was employed to evaluate the mechanical properties of carbon nanotube (CNT) reinforced PEEK nanocomposites. It was found that the weak interface between CNTs and the PEEK matrix leads to the flaws in the CNT/PEEK nanocomposite. A CNT-functionalization strategy was used to introduce H-bonds between CNTs and the PEEK matrix, improving the overall mechanical performance of the CNT/PEEK nanocomposite. Numerical examples validate that the addition of amino groups on CNTs can significantly improve the interfacial failure shear stress and elastic modulus of the CNT/PEEK nanocomposites. This mechanism study provides evidence and a theoretical basis to improve the mechanical performance of fiber-reinforced PEEK for lightweight structures in advanced equipment.